Sorta like a rock star - Quick, Matthew, 1973- (Little, Brown, 2011)
Amber Appleton, living in a school bus with her mom, refuses to give in to despair and continues visiting the elderly at a nursing home, teaching English to Korean women, and caring for a Vietnam veteran and his dog, but a fatal tragedy may prove to be one burden too many for the seventeen-year-old girl.